Proposed new interior design of New Straits Times Press (NSTP) office for NSTP (M) Berhad at LOT 9459N, NO.3 Greentown Business Centre, 30450 Ipoh, Perak / Nor Azizah Talkis - Talkis, Nor Azizah (Faculty of Architecture, Planning and Surveying, 2011)
The project that I’ve chosen for this final year project is proposed new design scheme of the New Straits Times Press (NSTP) Office for New Straits Times Press (M) Berhad. It is located at Lot 9459N, No.3 Greentown Business Centre, 30450 Ipoh, Perak . The main reason for this project is to come out with a new design which is more systematic in terms of its aesthetic value and space. It is also expected to meet the client requirements and provides more comfort in doing the activities inside the building. With this project, it is hoped that NSTP Berhad can be more productive and will eventually upgrade its image. Theme and concept are applied in the office space as to emphasize the space planning and also the corporate image of the company. The proposed concept and image is expected to give a positive impact towards the productivity of the staffs of the company. A few research are carried out to ensure the success of this project, which include research on site, interviews, observation, case study, and surveys. All method of research stated are to detect weaknesses and at the same time to solve problems. The research carried out are instilled in the process of designing, with a mission to produce an interesting and suitable corporate image of NSTP Berhad., be it in the funtional term or aesthetic term. As a challenge, I will try my best to come out with new, fresh ideas to design and upgrade the NSTP Berhad office so it will be an icon of Perak one day. In conclusion this proposal is the new design scheme which make the design process needs to be researched in every aspect required.